The efficacy of azathioprine for the treatment of inflammatory bowel disease: a 30 year review. - Fraser, A; Orchard, T; Jewell, D (2002)
BACKGROUND: There are limited data on factors predicting response to azathioprine and uncertainty regarding the optimal duration of treatment. PATIENTS AND METHODS: The notes of patients attending the Oxford IBD clinic from 1968 to 1999 were reviewed. Remission was defined as no need for oral steroids for at least three months and relapse was defined as active disease requiring steroids. RESULTS: A total of 622 of 2205 patients were treated with azathioprine (272 Crohn's disease, 346 ulcerative colitis, and four indeterminate colitis). Mean duration of the initial course of treatment was 634 days. The overall remission rates were 45% for Crohn's disease and 58% for ulcerative colitis. For the 424 patients who received more than six months of treatment, remission rates were 64% and 87%, respectively. Factors favouring remission were ulcerative colitis (p=0.0001), lower white blood cell (WBC) or neutrophil count (p=0.0001), higher mean cell volume (p=0.0001), and older age (p=0.05). For Crohn's disease, colonic disease favoured remission (p=0.03). Factors that were not significant were age, sex, lymphocyte count, and dose (mg/kg). The proportion of patients remaining in remission at one, three, and five years was 0.95, 0.69, and 0.55, respectively. The chance of remaining in remission was higher if WBC was less than 5 x 10(9) (p=0.03) and in male patients (p=0.01; Crohn's disease only). There was no difference in relapse rates between Crohn's disease and ulcerative colitis. After stopping azathioprine, the proportion of patients remaining in remission at one, three, and five years was 0.63, 0.44, and 0.35 (222 patients). Duration of azathioprine treatment did not affect the relapse rate after stopping treatment (p=0.68). CONCLUSIONS: Azathioprine is effective treatment for ulcerative colitis and Crohn's disease. The efficacy of azathioprine is reasonably well sustained over five years.